2022
DOI: 10.2147/copd.s382405
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Extrafine Single Inhaler Triple Therapy in Chronic Obstructive Pulmonary Disease (COPD) in Germany – The TriOptimize Study

Abstract: Purpose Real-word evidence on the effectiveness of switching from dual therapies or triple therapies (multiple inhalers) to extrafine single-inhaler triple therapy (efSITT), which consists of the inhaled corticosteroid (ICS) beclomethasone, the long-acting β 2 -agonist (LABA) formoterol and the long-acting muscarinic antagonist (LAMA) glycopyrronium, in patients with moderate-to-severe chronic obstructive pulmonary disease (COPD) is limited. The impact of switching to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(117 reference statements)
1
2
0
Order By: Relevance
“… 13 Importantly, ELLITHE study results on CAT score are in line with recent findings in a non-interventional study with a different, twice-daily SITT (beclomethasone/formoterol/glycopyrronium via pressurized metered dose inhaler). 45 In this study, improvements in CAT score of 2.7 units were observed, with similar overall baseline CAT scores (21.5 units), although the observation period of 6 months was considerably shorter than in ELLITHE.…”
Section: Discussionsupporting
confidence: 68%
“… 13 Importantly, ELLITHE study results on CAT score are in line with recent findings in a non-interventional study with a different, twice-daily SITT (beclomethasone/formoterol/glycopyrronium via pressurized metered dose inhaler). 45 In this study, improvements in CAT score of 2.7 units were observed, with similar overall baseline CAT scores (21.5 units), although the observation period of 6 months was considerably shorter than in ELLITHE.…”
Section: Discussionsupporting
confidence: 68%
“…A limitation of this questionnaire is the lack, so far, of an MCID in the literature; however, it is now a wellestablished tool in the real-life contest, and it is being more and more used to assess the level of adherence at different visits. 22,23,26 Moreover, the improvement in treatment adherence with extrafine triple therapy has been reported in other observational studies using the TAI score. 22,26,27 On average, the level of adherence reported in this study was already acceptable at the first visit (average score of 46.3).…”
Section: Discussionsupporting
confidence: 54%
“…22,23,26 Moreover, the improvement in treatment adherence with extrafine triple therapy has been reported in other observational studies using the TAI score. 22,26,27 On average, the level of adherence reported in this study was already acceptable at the first visit (average score of 46.3). This is probably explained by the fact that patients included in the study represent a cohort that has already started therapy with BDP/FF/G.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Real-world evidence on the occurrence of COPD exacerbations before and after initiation of SITT are lacking. A recent observational, noninterventional study in Germany demonstrated that patients with moderate-to-severe COPD with at least one exacerbation in the previous 12 months before switching to SITT (ICS/LAMA/LABA) from ICS/LABA (single or two inhalers) as part of routine clinical care experienced an improvement in health-related quality of life, lung function, and treatment adherence [ 13 ]. To our knowledge, there were no real-world studies evaluating the effectiveness of switching from dual therapy to SITT on reducing exacerbation frequency in US populations prior to the current study.…”
Section: Discussionmentioning
confidence: 99%